Hardiness Level of Students in Facing Learning Online During the Pandemic - Iyus Yosep; Cah Soniman Nitema Gea; Udin Rosidin; Rohman Hikmat (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Hardiness is a trait or personality of an individual with positive emotions for his physical and mental health. The COVID-19 pandemic has resulted in changes in learning methods, from offline to online. Readiness to adapt to online learning is a trigger for mental stress that affects the level of hardiness. Objective: This study aims to determine the level of hardiness in final year students of the 2018 Faculty of Nursing Universitas Padjadjaran (Unpad) in dealing with online learning during the pandemic. Method: Data collection was carried out from 17th -27th November 2021. The sampling technique in this study was random sampling. Data analysis used a quantitative study. The instrument used in this study is the Hardiness of Online Learning Period instrument. The research method used in this research is a descriptive quantitative method. The population used Faculty of nursing class of 2018 students, with a sample of 153 people calculated by the Slovin formula. Result: The results obtained indicate that most of the respondent have moderate hardiness (70,6%). Other result was found that the level of resilience and hardiness of respondents was in the medium category. Conclusion: This study shows that the respondents Most of the respondents have medium level of hardiness. students are expected to be able to maintain their hardiness during online learning and academics are expected to evaluate the applied learning. Nursing Implications: This study has implications, namely basic data for nurses to carry out nursing interventions in increasing hardiness in students at school.